Thermal degradation and thermal kinetic of SEBS block copolymer compatibilized PS/HDPE blends. (February 2023) - Ujcic, Massimo; Levak, Maja; Vranjes Penava, Nina; Govorcin Bajsic, Emi; Kosar, Vanja
The effect of styrene-ethylene/butylene-styrene block copolymer (SEBS) on the thermal degradation of polystyrene (PS)/high density polyethylene (HDPE) blends have been investigated. Polystyrene and (HDPE) are widely used thermoplastics, which have extensive application in everyday life. The main disadvantage of PS/PE systems is their poor miscibility which can be improved by adding compatibilizer. The blends were prepared by melt mixing in a twin screw extruder Haake Record 90. The behavior of the thermal degradation of PS/HDPE and PS/HDPE/SEBS blends has been investigated in inert nitrogen atmosphere by using thermogravimetric analysis (TGA) to obtain the degradation temperature and activation energy ( E a ). The E a for the PS/HDPE blends as well as for the PS/HDPE/SEBS blends was determined by the isoconversional Kissinger–Akahira–Sunose (KAS) method. The results indicated that the HDPE enhance thermal properties of the blends. The addition of SEBS in PS/HDPE blends increased the E a in all blends.